Museum Architecture : Texts and Projects by Artists. - Baselitz, Georg; Bill, Max; Buren, Daniel; Colquhoun, Alan; Cooke, Lynne; Dunst, Heinrich; Federle, Helmut; Francis, Mark; Fritsch, Katharina; Haerle, Christoph; Hafif, Marcia; Heerich, Erwin; et al. (Koln : Verlag der Buchhandlung Walther König, 2000)
Baselitz, Georg ; Bill, Max ; Buren, Daniel ; Dunst, Heinrich ; Federle, Helmut ; Fritsch, Katharina ; Haerle, Christoph ; Hafif, Marcia ; Heerich, Erwin ; Honegger, Gottfried ; Judd, Donald ; Kirkeby, Per ; Laib, Wolfgang ; Lüpertz, Markus ; Merz, Gerhard ; Morellet, François ; Pichler, Walter ; Serra, Richard ; Stella, Frank ; Venet, Bernar ; Walther, Franz Erhard ; Weibel, Peter ; Wigglesworth, Peter ; Zaugg, Rémy ; Zobernig, Heimo
bibliog. (eng.) p. 137-143, bibliog. (duits) p. 145-151
Duits & Engels
boek